Gallbladder Hodgkin Lymphoma: A Rare Case Report (Revista de Medicina Clinica, 2023)
We present an 81-year-old patient with a history of Acute Myeloblastic Leukemia treated 3 years earlier with the fludarabine, filgrastim and cytarabine regimen according to the 2014 Spanish Hematology Treatment Program regimen, with minimal residual disease negative after finishing treatment one year later. who went to the emergency room due to febrile syndrome and signs of acute cholecystitis, for which antibiotic therapy was started. 24 hours later, the evolution was unfavorable, so he was admitted to intensive care, an open cholecystectomy with Blake drainage was performed, however, the clinical worsening continued, and he died 72 hours later. The pathology results of the gallbladder showed lymphangitic infiltration by cells with atypia and expression of CD30, PAX5 and EBV-LMP1, concluding the diagnosis of gallbladder with infiltration by classic Hodgkin lymphoma. It is important to highlight that in the previously received treatment scheme, especially fludarabine, it produces significant myelosuppression and intense lymphopenia that has been related to the development of secondary neoplasms of both solid organs, leukemias, or lymphoproliferative syndromes. In conclusion, we believe that first of all patients with a history of chemotherapy treatment, the possibility of a second neoplasia should be taken into account in the differential diagnosis.
Keywords: Hodgkin Lymphoma; Gallbladder; Acute myeloblastic leukemia